Hydrophobic Deep Eutectic Solvent Based Dispersive Liquid–Liquid Microextraction for a Green and Efficient Triclosan Determination: Critical Study of Extraction Variables - Toledo-Neira, C; Toledo-Neira, C (Springer Nature, 2025)
A rapid and effective analytical method was developed for the detection of triclosan in wastewater samples using a hydrophobic deep eutectic solvent thymol-lidocaine (Thy-Lid, molar ratio of 1:1) and dispersive liquid–liquid microextraction (DLLME). The analyte was determined by high-performance liquid chromatography with a photodiode array detector (HPLC–PDA), obtaining a detection limit of 0.38 µg/L, a recovery rate of 99%, and an enrichment factor of the analyte in the water of 80. A factorial design was used to optimize the analytical signal to improve the time and reduce the cost of the method. Combining this chemometric optimization tool with a green solvent and DLLME allows for obtaining an analytical methodology aligned with the principles of green analytical chemistry, enabling the inexpensive, selective, and rapid analysis of triclosan in real wastewater. © The Nonferrous Metals Society of China 2025.